Diagnosis of celiac artery stenosis using multidetector computed tomography and evaluation of the collateral arteries within the mesopancreas of patients undergoing pancreaticoduodenectomy. Issue 7 (5th February 2021) - Ito, Kyoji; Takemura, Nobuyuki; Inagaki, Fuyuki; Mihara, Fuminori; Shida, Yoshitaka; Tajima, Tsuyoshi; Kokudo, Norihiro
Abstract: Introduction: Celiac artery (CA) stenosis (CAS), caused by various factors, is often asymptomatic because collateral blood flow from the superior mesenteric artery supplies the CA outflow region. The purpose of this study was to investigate the usefulness of multidetector computed tomography (MDCT) for diagnosing CAS and associated collateral artery formation, and elucidating the effect of CAS on the numbers and diameters of the arteries within the mesopancreas. Materials and Methods: We investigated 106 patients who underwent contrast‐enhanced MDCT, before pancreaticoduodenectomy, between January 2015 and September 2019. MDCT was used to determine the percentage stenosis of the CAs; patients were classified into CAS (−) (0–29% stenosis) and CAS (+) (30–100% stenosis) groups. The dissection lines of the mesopancreas were classed as Level I or II, and the numbers and diameters of the arteries along each dissection line were counted and measured. Results: There were 27 CAS (+) patients and 79 CAS (−) patients. In the CAS (+) group there were more arteries and they had larger diameters than those in the CAS (−) group, at both Levels I and II. There were significantly more arteries when the CA stenosis was ≥30% and they had larger diameters when the stenosis was ≥50%. Conclusions: MDCT is useful for diagnosing CAS, and CAS is associated with larger numbers and diameters of the arteries within the mesopancreas.